A Prospective Evaluation of Swallowing and Speech in Patients with Neurofibromatosis Type 2 - Rajendran, Sibi; Antonios, Joseph; Solomon, Beth; Kim, H. Jeffrey; Wu, Tianxia; Smirniotopoulos, James; Scott, Gretchen; Benzo, Sarah; Hayes, Christina; Heiss, John D.; Chittiboina, Prashant (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Neurofibromatosis type 2 (NF2) patients report that swallowing and speech problems significantly affect their quality of life, but the etiology of these phenomena is poorly understood. Swallowing and speech deficits may arise due to the neuropathy of involved nerves, due to posterior fossa tumor growth, or as iatrogenic effects from neurosurgical procedures to remove these tumors. This study aims to identify the natural history of swallowing and speech deficits in an NF2 cohort and to characterize the factors that may lead to those deficits.Methods Subjects (n = 168) were enrolled in a prospective, longitudinal study of NF2 with yearly imaging and clinical exams. The patients completed a self-reported questionnaire that included responses regarding subjective swallowing and speech dysfunction. A formal speech-language pathology evaluation and modified barium swallow (MBS) study (reported as American Speech-Language Hearing Association [ASHA] swallowing independency score from 1 through 7) was obtained when a speech/swallowing deficit was reported on the questionnaire.Results Of the 168 enrolled subjects, 55 (33%, median age = 31 years) reported subjective speech and/or swallowing deficits. These patients underwent one (n = 37) or multiple (n = 18) MBS studies during 44.8 ± 10.4 months follow-up. During MBS, a majority demonstrated near-normal swallowing (ASHA score >6, 82%), and no evidence of aspiration (aspiration/laryngeal penetration score = 1, 96%). Prior to initial MBS consultation, 38 (69%) patients had undergone relevant neurosurgical procedures. In those with recent (<1 week) posterior fossa surgery (n = 12), 2 (17%) patients had severe dysphagia and high aspiration risk on postoperative MBS. Both of these patients recovered to functionally independent swallowing status. Unilateral (n = 10) or bilateral (n = 6) tongue deficits unrelated to previous history suggestive of hypoglossal nerve injury were detected on clinical examination. There was a correlation between the presence of dysarthria and tongue deficits and tumors associated with the hypoglossal canal noted on imaging.Conclusion A large proportion of patients with NF2 report speech and swallow deficits that are not evident on objective measurements. We also found hypoglossal neuropathy unrelated to prior surgical interventions. Our findings suggest that swallowing and speech problems in NF2 are associated with lower cranial nerve neuropathy, some due to compressive effects of posterior fossa tumors. Adaptation over the course of the disease allows for the compensation of these deficits and subsequent normal findings on objective testing.
Keywords: Neurofibromatosis; NF2; swallowing; speech; hypoglossal nerve